Total cardiovascular events analysis of the EXAMINE trial in patients with type 2 diabetes and recent acute coronary syndrome. Issue 8 (16th August 2018) - Cavender, Matthew A.; White, William B.; Liu, Yuyin; Massaro, Joseph M.; Bergenstal, Richard M.; Mehta, Cyrus R.; Zannad, Faiez; Heller, Simon; Cushman, William C.; Cannon, Christopher P.
Abstract : Alogliptin, a dipeptidyl peptidase‐4 inhibitor, is approved for the treatment of patients with type 2 diabetes (T2DM). EXAMINE was a randomized controlled clinical trial designed to demonstrate the cardiovascular (CV) safety of alogliptin. In the trial, 5380 patients with established T2DM who had a recent acute coronary syndrome event (between 15 and 90 days) were randomized to treatment with either alogliptin or placebo. To better understand and describe the CV safety of alogliptin, we analyzed data from the EXAMINE trial to determine whether treatment with alogliptin affected recurrent and total CV events. Poisson regression analysis compared the total number of occurrences of CV death, MI, stroke, unstable angina, and coronary revascularization between all patients randomized to alogliptin vs placebo groups. Patients with recurrent CV events were older and more likely to have renal disease and history of heart failure. There were 1100 first CV events and an additional 666 recurrent events over a median of 18 months of follow‐up. There were no significant differences with regard to total number of events in patients treated with alogliptin (n = 873) or placebo (n = 893; P = 0.52). Furthermore, there were no differences in the types of events seen in patients treated with alogliptin or placebo. Alogliptin did not increase the risk of either first or recurrent CV events when compared with placebo in patients with T2DM and recent acute coronary syndrome. These data support the CV safety of alogliptin in patients who are at increased risk of future CV events.